Asymmetric cipher based on MPF and its security parameters evaluation - Mihalkovič, Aleksėjus; Sakalauskas, Eligijus (Lietuvos matematikos rinkinys, 2012)
The new asymmetric cipher algorithm based on matrix power function and matrix conjugation is presented. This algorithm is some alternative between known algorithms based on conjugacy problem, see e.g. Ko–Lee et al. and Anshel–Anshel–Goldfeld algorithm based on commutator concept. The security parameters are defined and their values are determined.
Keywords: asymmetric cyphering; matrix power function; one-way function